Oxidative stress status of highly prolific sows during gestation and lactation - Berchieri-Ronchi, C. B. [UNESP]; Kim, S. W.; Zhao, Y.; Correa, C. R. [UNESP]; Yeum, K. -J.; Ferreira, A. L. A. [UNESP] (Cambridge University Press, 2011)
Elevated oxidative stress is reported to be associated with pregnancy complications in highly prolific sows. Oxidative DNA damage and the antioxidant status were determined in blood samples collected during the course of gestation and lactation in multiparous sows. Blood samples were drawn from sows (n = 5) on days 30, 60, 90 and 110 of gestation (G30, G60, G90 and G110, respectively), on day 3, 10 and 18 of lactation (L3, L10 and L18, respectively) and on day 5 of postweaning (W5). Lymphocytes were isolated from the fresh blood and cryopreserved in each time point. Lymphocyte DNA damage was analyzed by alkaline single-cell gel electrophoresis (comet assay) to determine the single-and double-strand brakes and endogenous antioxidant concentrations using an HPLC system with UV detection. The comet assay showed elevated (P < 0.05) DNA damage (between 38% and 47%) throughout the gestational and lactational periods than during early gestation (G30; 21%). Plasma retinol concentration was reduced (P < 0.05) at the end of gestation (G110) compared with G30. Plasma alpha-tocopherol concentrations also showed a similar trend as to retinol. This study indicates that there is an increased systemic oxidative stress during late gestation and lactation, which are not fully recovered until the weaning compared with the G30, and that antioxidant nutrients in circulation substantially reduced in the mother pig at G110.
Keywords: antioxidant; DNA damage; oxidative stress; sows